A Crystallization and Melting of Glass with Ln\(_2\)Si\(_2\)O\(_7\)/mullite Eutectic Composition - Shunkichi Ueno (Chemical and Materials Sciences: Developments and Innovations Vol. 7, 2024)
This chapter summarizes the results of the author’s previous work on the technique of producing film with eutectic microstructure by heat treatment of a glass with Ln2Si2O7/Al6Si2O13 (Ln=Y and Yb) eutectic composition. Some new experimental data on post-crystallization melting phenomena were presented and combined with previous data to discuss glass crystallization and melting. In this chapter, the topic of crystallization of glass with Ln2Si2O7/Al6Si2O13 eutectic composition is discussed. In the Y2O3-SiO2-Al2O3 ternary phase diagram, there is a broad region of easy vitrification. The vitrification region exists on the straight line connecting between stoichiometric compound Ln2Si2O7 and Al6Si2O13 phases. It is suggested that the vitrified region contains eutectic Ln2Si2O7 (Ln=Y, Yb) and Al6Si2O13 phases. The melt with the eutectic composition was quenched to obtain glass. The samples showed two exothermic peaks at temperatures higher than the glass transition temperature. At the first step of the exothermic peak in the case of Ln=Y, the Y2Si2O7 phase crystallized from the bulk glass surface. The Al6Si2O13 phase also crystallized during the second stage of the exothermic peak. The activation energy of crystallization in the first stage for Ln=Y, determined by Kissinger’s plot, was 772.1 kJ/mol, and that for Ln=Yb was 632.3 kJ/mol. On the other hand, the activation energy for the second stage of crystallization was 353.1 kJ/mol for the Ln=Y sample and 598.8 kJ/mol for the Ln=Yb sample. For the purpose of comparing the ease of crystallization of the Y2Si2O7 phase and Al6Si2O13 phase from a different perspective, this time, the melting and crystallization of compositions that deviated from the eutectic composition were investigated. For the Ln=Y sample, three exothermic peaks appeared when the composition was shifted from the eutectic composition to the Y2Si2O7 side. The intensity of the first exothermic peak increased. On the other hand, when the composition was shifted from the eutectic to the Al6Si2O13 side, two exothermic peaks were observed. Even in this case, the first exothermic peak was larger. Post-crystallization melting began at 1320°C, 30°C lower than the reported melting point. Two endothermic peaks were observed at the melting point. This suggests that the phenomenon of re-crystallization and further re-melting occurred after melting. In the case of Ln=Yb, a small amount of alumino-silicate phase with a ZSM5-type zeolite structure was observed as an intermediate phase after heat treatment at 1000°C. Even at temperatures 250°C below the melting point, the sample deformed significantly due to viscous flow. However, a eutectic microstructure formed inside the bulk sample. After heat treatment at 1450°C which is the melting point of the eutectic, fine eutectic microstructure was formed throughout the bulk sample. The microstructure in the center of the bulk was finer than that near the bulk surface. For the purpose of investigating techniques to form film with eutectic microstructure using viscous flow and crystallization of glass, we have newly evaluated the viscous flow properties of the eutectic composition glass. By applying a powder sample of Ln=Yb glass on a sintered Al6Si2O13 substrate and annealed at 1450°C, a film with a fine Yb2Si2O7/Al6Si2O13 eutectic microstructure was formed. The eutectic structure grew directly from the substrate mullite. A eutectic film with excellent adhesion could be formed. Crystallization of the glass bulk and viscous flow of the glass occur almost simultaneously.